The Senussi movement in Libya and its relationship with the Ottomans and French in Algeria1202) -1276 AH /1787-1859 AD( (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
This research presents a brief study of the Senussi movement in Libya during the reign of its founder, Muhammad ibn Ali al-Sanusi. This occurred in light of Libya's subjection to Ottoman control and the French occupation of Algeria on the one hand, and the religious, political and social decline that the Islamic world suffered from, which led to a unified sense of the need for reform on the other hand. The personality of its founder, Muhammad ibn Ali al-Sanusi, and his scientific journeys, which he undertook to acquire knowledge and spread his teachings and preaching, were first introduced. Then, the method of its emergence was studied, with an explanation of its objectives and the factors that led to its establishment. In addition, the political dimension of the Senussi movement was studied, which was manifested in the consolidation of its relationship with the Ottoman Empire through the wise policy followed by Muhammad ibn Ali al-Sanusi in dealing with it as a caliphate state. The political dimension was also evident in the study of its role in resisting the French occupation of Algeria, which provided all the support the resistance needed, until the Senussi movement considered itself responsible for all types of resistance that took place against the French occupation, and that it was the cause of all the revolutions that took place against France.
Keywords: Muhammad ibn Ali al-Sanusi, Libya, Ottoman Empire, French occupation, Algeria.